Environmental Cooperation in Conflict Zones: Riparian Infrastructure at the Armenian–Turkish Border. (September 2019) - Altingoz, Mehmet; Ali, Saleem H.
Due to historical grievances, Armenia and Turkey experience severe international conflicts and do not maintain diplomatic ties. Yet, as a vestige of the Soviet period, when Armenia was not an independent country, both nations share the Arpacay/Akhuryan Dam, and riparian cooperation exists at the local level. We observed that local cross-border water institutions are authorized to manage the dam and do so via polycentric management principles. We suggest that such a devolved model of governance facilitates this unique cooperation. Furthermore, there is a positive relationship between private management of water resources in such areas and the ability to sustain cooperation. However, so far, the positive impacts of this cooperation on improving international relations have been little, if any. We suggest that what makes cooperation possible in this context also inhibits its expansion to broader peacebuilding. We also suggest that increased localization of management, coincident with improved relations, maximizes cooperation potential.